Assessing Psychopathic Traits and Criminal Behavior in a Young Adult Female Community Sample Using the Self‐Report Psychopathy Scale1. Issue 4 (21st April 2015) - Declercq, Frédéric; Carter, Rachel; Neumann, Craig S.
Abstract This study assessed psychopathic traits in a nonforensic female population (N = 343). Respondents completed the Self‐Report Psychopathy Scale‐4: Short Form (SRP‐SF) and also reported on their Criminal Behavior. The results revealed relatively higher scale elevations for the Interpersonal and Lifestyle SRP‐SF facets, compared to the Affective and Antisocial facets. Also, those with a history of Criminal Behavior had significantly higher SRP‐SF facet scores on all four psychopathy domains, compared to those without such history. Consistent with a number of previous studies, the structural equation modeling results revealed good fit for the four‐factor SRP‐SF model. In addition, a super‐ordinate SRP‐SF factor, which accounted for the majority variance of all four SRP‐SF first‐order factors, also accounted for 50% of the variance in a latent Criminal Behavior factor. Taken together, findings support use of the SRP‐SF to assess psychopathic features in a moderately large sample of Belgium women.